A Perspective Beyond the Psychiatry World - Binti Ibrahim, Nur Aifiah (Islamic Counseling: Jurnal Bimbingan Konseling Islam, 2025)
After a thorough evaluation, there is a repulsive attack for the passengers to hold another meeting to call it quits. The never-ending trials and tribulations that excuse someone from being beaten and disqualified from a triumph. The psychosis and psychedelic impairment to have another debate over the heated discussion for the foreigners to seek the truth behind the handlebar examination department. As the person is, his or her health condition is prescribed to be another schizophrenic condition to be reevaluated by a group of practitioners in line with their high hopes. Hope it was not a delay in treatment, as the strategies to take care of their mindless body operate like a timely clock. By beating around the bush, they are in their highest position for the subconscious mind to predict what is happening in the future. By having the courage and wisdom to speak louder than words, they are taking a more direct approach when dealing with a psychological problem. Hence, a pseudoscience belief may affect the delay of the actual treatment and diagnosis of the psychological problem that is harmful in nature. Due to a lack of a scientific approach when trying to overcome anxiety, fear, and depression.